Re-evaluating cost effectiveness of universal meningitis vaccination (Bexsero) in England: modelling study - Christensen, Hannah (BMJ Publishing Group Ltd., 2014)
Objective To use mathematical and economic models to predict the epidemiological and economic impact of vaccination with Bexsero, designed to protect against group B meningococcal disease, to help inform vaccine policy in the United Kingdom. Design Modelling study. Setting England. Population People aged 0-99. Interventions Incremental impact of introductory vaccine strategies simulated with a transmission dynamic model of meningococcal infection and vaccination including potential herd effects. Model parameters included recent evidence on the vaccine characteristics, disease burden, costs of care, litigation costs, and loss of quality of life from disease, including impacts on family and network members. The health impact of vaccination was assessed through cases averted and quality adjusted life years (QALYs) gained. Main outcome measures Cases averted and cost per QALY gained through vaccination; programmes were deemed cost effective against a willingness to pay of £20 000 (€25 420, $32 677) per QALY gained from an NHS and personal and social services perspective. Results In the short term, case reduction is greatest with routine infant immunisation (26.3% of cases averted in the first five years). This strategy could be cost effective at £3 (€3.8, $4.9) a vaccine dose, given several favourable assumptions and the use of a quality of life adjustment factor. If the vaccine can disrupt meningococcal transmission more cases are prevented in the long term with an infant and adolescent combined programme (51.8% after 30 years), which could be cost effective at £4 a vaccine dose. Assuming the vaccine reduces acquisition by 30%, adolescent vaccination alone is the most favourable strategy economically, but takes more than 20 years to substantially reduce the number of cases. Conclusions Routine infant vaccination is the most effective short term strategy and could be cost effective with a low vaccine price. Critically, if the vaccine reduces carriage acquisition in teenagers, the combination of infant and adolescent vaccination could result in substantial long term reductions in cases and be cost effective with competitive vaccine pricing.